Who Moves The Malaysian Stock Market The U.S. Or Japan? - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
This pap e r examines long rt(IF consovenrents between Ailalaysian stock marker and the two largest stock markets the world: the U.S. and Japan. By employing time-â¢eries analysis, i,eâ evintegration. variance decompositions, and impulse responsefUnctions. the paper seeks to investigate %thich market actually leads the Malaysian stock marker before. during, and after the 1997 Asian financial crisis periods. The results indicate that there is a comoventent of these markets only in the post Crisis period. The Japanese stock market is found to significantly Move the Malaysian stock market compared to U,S. stock market for the postâ¢crisis period. At the same time, there seems to be a growing proportion of bilateral trade between Malaysia and Japan during the mentioned period. This finding seons to be cwrsis-tent with the view that the stronger the bilateral trade ties between two countries. the higher the degree of cbmoventents (Masilr and Masih 1999